EFFECT OF HYDROSTATIC WATER PRESSURE ON PERFORMANCE OF SELF-COMPACTING CONCRETE PLACED UNDERWATER - Ali T. Jasim; Maryam A. Ali (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2018)
This study has focused on investigation of effect of hydrostatic pressure on the properties of underwater self-compacting concrete. In this research, 30 mixes of self-compacting concrete have been prepared with six groups. The first three groups contain AWA (Anti Washot Admixture), while the second groups made without AWA. The main parameters explored in this research were: silica fume, limestone powder and rice husk ash as a cement replacement content with 0% and 1% anti washout admixture and different water depth (10 ,20, 30 ,40 and 50 m). Washout loss was found by using either the CRD C61 test method or a newly developed device for simulation of increased hydrostatic pressure on the concrete/water interface. Good correlations were investigating between the standard washout loss determined according to CRD C61 and simulated threshold water head and corresponding maximum washout loss.